Expression Pattern of ERF Gene Family under Multiple Abiotic Stresses in Populus simonii × P. nigra - Yao, Wenjing; Zhang, Xuemei; Zhou, Boru; Zhao, Kai; Li, Renhua; Jiang, Tingbo (Frontiers in Plant Science, 2017)
Identification of gene expression patterns of key genes across multiple abiotic stresses is critical for mechanistic understanding of stress resistance in plant. In the present study, we identified differentially expressed genes (DEGs) in di-haploid Populus simonii × P. nigra under respective stresses of NaCl, KCl, CdCl2, and PEG. On the basis of RNA-Seq, we detected 247 DEGs that are shared by the four stresses in wild type poplar, and mRNA abundance of the DEGs were validated in transgenic poplar overexpressing ERF76 gene by RNA-Seq and RT-qPCR. Results from gene ontology analysis indicated that these genes are enriched in significant pathways, such as phenylpropanoid biosynthesis, phenylalanine metabolism, starch and sucrose metabolism, and plant hormone signal transduction. Ethylene response factor (ERF) gene family plays significant role in plant abiotic stress responses. We also investigated expression pattern of ERF gene family under the four stresses. The ERFs and DEGs share similar expression pattern across the four stresses. The transgenic poplar is superior to WT in morphologic, physiological and biochemical traits, which demonstrated the ERF76 gene plays a significant role in stress resistance. These studies will give a rise in understanding the stress response mechanisms in poplar.